Histomorphometric Analysis of Heparin Effects on the rhBMP-2 - Jung, Myung Ho; Lee, Chong Heon (The Korean Journal of Oral and Maxillofacial Pathology, 2016)
Although recombinant human Bone Morphogenetic Proteins-2 (rhBMP-2) is clinically useful for bone regeneration, induction of new bone formation requires a large amount of rhBMP-2 in humans. Many investigators have been concentrated efforts on searching materials which enhance the effect of rhBMP-2, and then heparin was found as a potentiating material to rhBMP-2. The purpose of this study were histomorphometrically to analyze the enhancing effect of heparin to rhBMP-2 and to study the mode of actions of heparin to rhBMP-2. Stem cells obtained from rabbit adipose tissue were divided into 4 groups according to heparin concentrations(0, 0.25, 2.5, and 25 μg/ml) with a constant rhBMP-2 concentration(150 ng/ml) and cultured for 2, 4, and 8 days. Naphtol AS phosphate-fast blue BB staining for alkaline phosphatase content and Alizarin red staining for calcium content were performed as time schedules and the morphology and osteoblastic activity were observed closely. 5 μg/ml rhBMP-2 was mixed with the following doses of heparin: 0, 0.25, 2.5, and 25 μg/ml. Each mixture was blotted into 0.5 g of multiporous anorganic bovine bone and was inserted into the critical sized calvarial defects(diameter of 0.8-mm) of rabbits. After 1, 3, and 6 weeks, the harvested tissues were processed and stained using H&E and Masson’s trichrome methods. And the areas of newly formed bone in the grafted material were measured and statistically analyzed. During culture experiment of adipose stem cells with rhBMP-2 and heparin, the degree of osteoblastic differentiation was increased with increasing heparin concentration, but the cellular degeneration was accelerated at higher concentration of heparin as time passed. Consequently the osteoblastic differentiation of progenitor cells were accelerated as the concentration of heparin increased. In addition, the progenitor cells exhibited full differentiations early showing fast degeneration. The higher the concentration of heparin, larger newly formed bone in grafted materials was obtained in initial period. However, the increased amount of the newly formed bone in grafted materials was progressively decreased at the higher concentration of heparin as time passed. In conclusion, the heparin has influence on the osteoinductive effect of rhBMP-2 in the initial stage of bone formation. The use of heparin with rhBMP-2 could offer cheaper, safer, and improve clinical results in grafting procedures. KCI Citation Count: 0